Temporal dynamics of invertebrate groups in the techno-lands of the Nikopol manganese ore basin - Babchenko, Anna; Tymchyi, Kateryna; Sidashenko , Olha (Problems of Environmental Biotechnology, 2021)
The established types of temporal dynamics of invertebrates indicate the presence of complex and formed processes of animal population regulation in relatively young ecological formations, which are techno-soils.